Cuapetes yapiensis sp. nov. (Crustacea: Decapoda: Pontoniinae), a new mangrove shrimp from Yap, Caroline Islands - Bruce, A. J. (Zootaxa, 2013)
A new pontoniine shrimp species, Cuapetes yapiensis, from mangroves at Quamun, on Yap Island, Caroline Islands, is described and illustrated. Cuapetes yapiensis most closely resembles C. darwiniensis Bruce. Six species of Cuapetes are now known from the Caroline Islands.